2019
DOI: 10.1016/j.jad.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and network analysis of depressive symptoms in patients with cancer compared to the general population

Abstract: License: Article 25fa pilot End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
39
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 40 publications
11
39
2
9
Order By: Relevance
“…These findings are similar to previous PHQ-9 network studies in cancer patients 19 , which indicate a greater centrality in reagent 4 (energy loss), which may suggest an indirect relationship of this symptom in people with an irreversible chronic disease.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to previous PHQ-9 network studies in cancer patients 19 , which indicate a greater centrality in reagent 4 (energy loss), which may suggest an indirect relationship of this symptom in people with an irreversible chronic disease.…”
Section: Discussionsupporting
confidence: 90%
“…Studies most frequently estimated either one (n=7; Boschloo et al, 2016;Kendler et al, 2018;McWilliams et al, 2017;Park & Kim, 2020;Santos et al, 2017;van Loo et al, 2018;Wasil et al, 2020) or two networks (n=8; Airaksinen et al 2020;Bos et al 2018;de la Torre-Luque et al, 2020;Fried et al 2016;Hakulinen et al 2020;Hartung et al 2019;Schweren et al 2018;van Borkulo et al 2015). The rationale for constructing multiple networks consisted of making group-level comparisons (n=10; An et al, 2019;Cramer et al, 2012;de la Torre-Luque et al, 2020;Fried et al, 2016;Hakulinen et al, 2020;Hartung et al, 2019;Mullarkey et al, 2019;Murri et al, 2018;Osborn et al, 2020;Schweren et al, 2017), or measuring within-group MDD differences over time in the context of treatment interventions (n=6; Airaksinen et al, 2020;Berlim et al, 2020;Bos et al, 2018;Madhoo & Levine;McElroy et al, 2019;van Borkulo et al, 2015).…”
Section: Network Characteristicsmentioning
confidence: 99%
“…Groups were tested for differences in their MDD network structure (n=10 studies; 31 networks), with significant differences primarily found in community samples. Specifically, between males and females in adolescent depression (Mullarkey et al, 2019), communitydwelling older adults from Spain and Nigeria (de la Torre-Luque et al, 2020), and cancer patients and the general population (Hartung et al, 2019). Only one clinical sample (Berlim et al, 2020) reported significant group differences: before and 8 weeks after an antidepressant treatment (escitalopram and desvenlafaxine).…”
Section: Network Characteristicsmentioning
confidence: 99%
“…A typical empirical approach adopted within this framework is to gather data from a large number of individuals about a wide variety of symptoms through the use of self-report instruments and then to systematically examine the patterns of association among symptoms. This approach can also be used contrastively to assess the way in which these patterns of association differ among different populations (e.g., Hartung, Fried, Mehnert, Hinz, & Vehling, 2019).…”
Section: Perspectives On Symptomsmentioning
confidence: 99%
“…Implicit in this concept is a culturally embedded normative judgment about the value of viewing oneself positively. However, in nonclinical samples, there are systematic differences in reported levels of self-esteem across cultures and even generations, and as a consequence, low reported self-esteem has stronger associations with psychopathology in some cultures than others (Gentile, Twenge, & Campbell, 2010; Heine, Lehman, Markus, & Kitayama, 1999; Schmitt & Allik, 2005).…”
Section: Research Implications and Future Recommendationsmentioning
confidence: 99%